PENGARUH CITRA MEREK DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN PADA BRAND JEANNE ARTHES PARFUM PT.MATAHARI DEPARTEMENT STORE MALL LEMBUSWANA SAMARINDA - Fitriani, Robin Jonathan, Adisthy Shabrina Nurqamarani (LPPM University 17 Agustus 1945 Samarinda, 2018)
This research aims to identify: 1) brand image of purchase decision on Jeanne arthes perfume brand, 2) price to purchase result on Jeanne arthes perfume brand, 3) brand image and price to purchase decision of Jeanne arthes perfume brand. The research population is all customers of perfume brand of Jeanne Arthes PT. Matahari Department Mall Lembuswana Samarinda. Samples are 96 respondents with Unknown population and sample selection using Incidental Sampling technique. Variables in this research are 3 that are brand image, price and purchase decision. Data analysis technique used is multiple linear regressions with classical assumption test and hypothesis testing. The finding of the researsh shows that brand image and price affect positive and significant to purchase decision on the brand Jeanne Arthes Perfume PT. Matahari Department Store Mall Lembuswana Samarinda. , variable of brand image and price simultaneously have positive and significant effect to purchase decision on Jeanne Arthes perfume brand of PT. Matahari Department Store Mall Lembuswana Samarinda. Forfuther research is expected that the next researcher can use other product brands and/or other independent variables so that more findings are identified.